Vehicular and industrial sources of PGEs, Au and Ce in surface soil and roadside soils and dusts from two cities of Turkey - Özen, Murat; Özen, Songül Akbulut; Çevik, Uğur (Sakarya University, 2021)
In this study, rhodium, palladium, platinum, gold and cerium were determined by ICP-MS after trace-matrix separation in roadside dusts and soil samples along different motorways in Ankara and Bursa, and in soil samples taken from industrial locations in Nilüfer, Bursa. The clear presence of Pd and Rh was determined at different traffic locations. Platinum remained below the method’s quantification limit for most of the samples. Results showed that both cities showed relatively high concentrations of; Rh and Pt in tunnels and downtowns, Pd in tunnels, bus stations and crossroads, and Au in downtowns. Consistent with the daily road traffic, relatively high concentrations of Rh, Pd and Pt were determined for Ankara. Based on the limited data available for Pt, Pt:Pd ratios varied between 0.04 and 0.25, and Pt:Rh ratios varied between 0.59 and 2.1. Measurements at the industrial location showed an average Rh and Pd concentration of 11 and 359 µg/kg, respectively. On the other hand, Au concentrations remained below the method’s quantification limit except for one sampling location. The average Ce concentration was determined as 23 mg/kg. Platinum remained below the method’s quantification limit for all industrial sampling locations. Overall, high average Rh and Pt concentrations were determined at the traffic sites, while higher average Pd concentration was determined at the industrial locations. Cerium remained consistently below the earth’s crustal levels, which infers that no anthropogenic source can be attributed to Ce.
Keywords: Environmental Sciences; Çevre Bilimleri [EN] Metrology; Applied and Industrial Physics; Metroloji; Uygulamalı ve Endüstriyel Fizik